Engineering Polysaccharide‐Based Hydrogel Photonic Constructs: From Multiscale Detection to the Biofabrication of Living Optical Fibers (Adv. Mater. 52/2021). Issue 52 (27th December 2021) - Guimarães, Carlos F.; Ahmed, Rajib; Mataji‐Kojouri, Amideddin; Soto, Fernando; Wang, Jie; Liu, Shiqin; Stoyanova, Tanya; Marques, Alexandra P.; Reis, Rui L.; Demirci, Utkan
Abstract : Digitalizing Biology The living hydrogel optical fibers and polysaccharide‐based photonic constructs fabricated by Rui L. Reis, Utkan Demirci, and co‐workers in article number 2105361 are highly versatile and enable the screening of multiscale phenomena, from macro‐level forces and shapes to nano‐level biotarget detection. Living optical interactions further allow the direct quantification of dynamic cellular responses, ranging from metabolism to 3D proliferation and anti‐cancer drug susceptibility—asking cells the right question.